2019
DOI: 10.1002/pen.25071
|View full text |Cite
|
Sign up to set email alerts
|

3D Viscoelastic Simulation of Jetting in Injection Molding

Abstract: A three‐dimensional model and algorithm were proposed to simulate the jetting phenomenon in injection molding. The Giesekus model was employed to describe the viscoelastic behavior of the incompressible, non‐isothermal polymer flow, and the volume of filling method was used to track the jetting free surface and advancing melt front. The governing and constitutive equations were discretized by finite volume method. To improve the precision and stability of the numerical method, a modified pressure implicit with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In this section, the governing equations (mass, momentum, energy, and constitutive equations) for polymer melt are discretized by the finite volume method on collocated mesh. The Equations ( 1), ( 18), (19), and ( 20) can be rewritten in the following general form 37…”
Section: Finite Volume Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, the governing equations (mass, momentum, energy, and constitutive equations) for polymer melt are discretized by the finite volume method on collocated mesh. The Equations ( 1), ( 18), (19), and ( 20) can be rewritten in the following general form 37…”
Section: Finite Volume Methodsmentioning
confidence: 99%
“…The Pom‐Pom model and Rolie‐Poly model are suitable for characterizing the rheological behaviors of branched and linear polymer melts. More and more simulation results of the filling process of injection molding based on viscoelastic constitutive equations have been reported in the last decade 13–20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The macroscopic simulation of injection molding has been researched and developed for decades, and many simulation methods have been proposed. The mainstream method for injection molding filling simulation is the mesh-based approaches [ 3 , 4 ]. The most popular injection molding engineering software Moldflow uses the finite element method (FEM), and Modex3D uses the finite volume method (FVM).…”
Section: Introductionmentioning
confidence: 99%
“…Though it has been reported that polymeric fluids behaved strong turbulence due to viscoelastic character [17]; moreover, Balkovsky [18] found that the turbulent effect can reach the turbulent flow with Re = 5000. Recently, Zhang [19] viscoelastic numerical simulated jetting phenomenon during injection and found elasticity had an effect on the evolution of buckling during jetting.…”
Section: Introductionmentioning
confidence: 99%